Examining the relationships between challenge and threat cognitive appraisals and coaching behaviours in football coaches - Dixon, M.; Turner, M. J.; Gillman, J. (Journal of Sports Sciences, 2017)
Previous research demonstrates that sports coaching is a stressful activity. This article investigates coaches` challenge and threat cognitive appraisals of stressful situations and their impact on coaching behaviour, using Blascovich and Mendes` (2000) biopsychosocial model as a theoretical framework. A cross-sectional correlational design was utilised to examine the relationships between irrational beliefs (Shortened general attitude and belief scale), challenge and threat appraisals (Appraisal of life events scale), and coaching behaviours (Leadership scale for sports) of 105 professional football academy coaches. Findings reveal significant positive associations between challenge appraisals and social support, and between threat appraisals and autocratic behaviour, and a significant negative association between threat appraisals and positive feedback. Results also show that higher irrational beliefs are associated with greater threat, and lesser challenge cognitive appraisals. However, no associations were revealed between irrational beliefs and challenge cognitive appraisals. Additionally, findings demonstrate a positive relationship between age and training and instruction. Results suggest that practitioners should help coaches to appraise stressful situations as a challenge to promote positive coaching behaviours.